2023
DOI: 10.1021/acs.jctc.3c01082
|View full text |Cite
|
Sign up to set email alerts
|

Multimer Embedding Approach for Molecular Crystals up to Harmonic Vibrational Properties

Johannes Hoja,
Alexander List,
A. Daniel Boese

Abstract: Accurate calculations of molecular crystals are crucial for drug design and crystal engineering. However, periodic high-level density functional calculations using hybrid functionals are often prohibitively expensive for the relevant systems. These expensive periodic calculations can be circumvented by the usage of embedding methods in which, for instance, the periodic calculation is only performed at a lower-cost level and then monomer energies and dimer interactions are replaced by those of the higher-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Hoja et al developed and evaluated an approach to accelerate the prediction of energies, forces, etc. of higher level electronic structure methods for molecular crystals via a multimer embedding approach . Weng et al demonstrated how to efficiently and robustly obtain regionally localized orbitals for a subsystem using the generalized Pipek-Mezey scheme, which can be applied to large nanoscale systems without incurring significant computational cost overhead .…”
mentioning
confidence: 99%
“…Hoja et al developed and evaluated an approach to accelerate the prediction of energies, forces, etc. of higher level electronic structure methods for molecular crystals via a multimer embedding approach . Weng et al demonstrated how to efficiently and robustly obtain regionally localized orbitals for a subsystem using the generalized Pipek-Mezey scheme, which can be applied to large nanoscale systems without incurring significant computational cost overhead .…”
mentioning
confidence: 99%